O emprego de recursos metalinguísticos no Twitter - Mattos, Luiz Felipe (2022)
The present work aims to analyze metalanguage as a cognitive technology and its representations through the reading and writing of tweets – posts on the social network Twitter in which informal interactions occur through written language. Therefore, this work begins its discussions with the theoretical articulation of language and technology, linked to the concept of language as a system proposed by Cupani (2004; 2011), also showing the writing as a technology (AUROUX, 1992; COULMAS, 2014; GNANADESIKAN, 2009). After that, we discuss Dascal’s proposal (2002), in which the author considers language as a cognitive technology. It is important to stimulate reflection jointly on the concepts of epilanguage (CULIOLI, 1995; CULIOLI & NORMAND, 2005; ROMERO, 2011; 2019) as non-rational knowledge that is inaccessible to the speaker in order to later discuss metalanguage (AUROUX, 1992; JAKOBSON, 2010; FLÔRES, 2011; FLÔRES; GABRIEL, 2012) – the latter as linguistic knowledge ordered and externalized by the speaker at the moment of enunciation. In this research, the idea of metalanguage as a cognitive tool is defended, as it is understood that the speaker can reflect on the language through its representations, taking into account their linguistic repertoire from certain context(s) (DASCAL, 2006). As a methodology for data collection and analysis, we opted for a descriptive and interpretive approach to organizing a corpus consisting of tweets from users on the digital social network Twitter. For the composition of this corpus, tweets that addressed any linguistic analysis made by users were collected. Thus, this research reflects on the manifestation of metalinguistic knowledge in tweets, noting that this media has limited characters and, thus, it may be interesting to find out how the speaker can think about the uses of the language and try to expose them even with the limitation of this type of writing. To do só, we observe the understanding and inquiry creatively made by the speakers. The results indicated by the analysis show the technical nature of epilanguage through the traces of unconscious activity in the production of tweets, using metalanguage as a technology to represent their linguistic reflections in the digital social network.